Realization of Wireless-Controlled Gear Shifter for Shaft-Driven Bicycle Gearbox - Hsiung-Cheng Lin; Elangovan Chelliah (Machines)
Cycling is now a very popular sport and leisure activity or commuting tool around the world, with its popularity growing especially during the epidemic. The traditional bicycle depends on a chain driving mechanism to move forward (This paper is an extended version of our paper published in The 16th Intelligent Living Technology Conference, Taichung, Taiwan, 2 June 2022). However, its transmission chain is easily dirtied and loosened so that regular maintenance is highly demanded to sustain normal function. To achieve the idea of maintenance-free, self-calibrating, and efficient mechanism operation, a wireless-controlled gear shifter for shaft driven bicycles is proposed, not only to overcome the limitations of the traditional chain driving mechanism, but also to make riding control more convenient. Firstly, an actuated gear shifter module coordinated with the gear positioning system was designed. Secondly, a remote controller module with information organic light-emitting diodes (OLEDs) and shift operation buttons was developed. Both modules use independent batteries and a Bluetooth Low Energy (BLE) interface to communicate with each other for wireless shifting control. The experimental results verify the effectiveness of the proposed system in terms of accuracy, rapidness, and robustness.